Analisis Penerapan Space Matrix Pada Bank BRI Unit Sokaraja Tengah Dalam Menciptakan Inovasi Layanan Perbankan untuk Segmen Mikro dan UMKM - Septianingsih, Leny; Ashfa, Muhammad Aqila; Aviana, Nagita Lyra; Shafrani, Yoiz Shofwa (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
The rapid advancement of digital transformation, coupled with the increasing intensity of competition in the financial industry, compels banking institutions to implement appropriate strategies to enhance their competitiveness—particularly in serving the micro and Small and Medium Enterprises (SMEs) segments. This study aims to analyze the application of the Strategic Position and Action Evaluation (SPACE) Matrix as a tool for formulating effective marketing strategies at Bank BRI Unit Sokaraja Tengah.By employing a qualitative approach through direct observation and interviews, this research evaluates four key dimensions within the SPACE Matrix framework: Financial Strength (FS), Competitive Advantage (CA), Environmental Stability (ES), and Industry Strength (IS). The analysis results indicate that FS scored 5, CA scored 4, ES scored 4, and IS scored 3. Collectively, these scores position Bank BRI Unit Sokaraja Tengah within the aggressive quadrant.These findings suggest that the bank unit possesses strong internal capabilities and significant external opportunities for continued growth and innovation. Based on this strategic positioning, the recommended strategies include: strengthening digital service innovation, enhancing customers' financial literacy, and fostering active collaboration with the SME community. The implementation of this aggressive strategy is expected to reinforce the bank's competitive position and sustainably support growth in the microeconomic sector.